A pilot study of an emotional intelligence training intervention for a paediatric team. Issue 2 (13th October 2016) - Bamberger, Ellen; Genizi, Jacob; Kerem, Nogah; Reuven-Lalung, Ayalla; Dolev, Niva; Srugo, Isaac; Rofe, Amnon
Abstract : Objective: Emotional intelligence (EI) is the individual's ability to perceive, understand and manage emotion and to understand and relate effectively to others. We examined the degree to which EI training may be associated with a change in EI among different medical personnel and patient satisfaction. Design, setting and participants: The EI of 17 physicians and 10 nurses in paediatric ward was prospectively evaluated with Bar-On's EI at baseline and after 18 months. 11 physicians who did not undergo the intervention served as controls. Interventions: The intervention consisted of a training programme comprising group discussions, simulations and case studies. Main outcomes and measures: Pre-emotional quotient inventory (EQ-i) and post-EQ-i scores and patient satisfaction surveys of nurse and physicians pre-intervention and post-intervention were analysed. Results: The mean overall EI score of the study sample rose from 99.0±9.6 (both plus and minus mathematical operations standing for SD) at baseline to 105.4±10 (p<0.000) after 18 months, with the most robust increase (nearly 6%; p<0.003) manifested among physicians. In contrast, the control group's EI scores did not change over this period. Within the intervention group, physicians displayed a statistically significant increase in three of the five EI dimensions, compared with only one of the five EI dimensions for nurses. Patient satisfaction scores relating to physician care rose from 4.4 pre-intervention to 4.7 post-intervention (p=0.03). Conclusion: An EI intervention led to an overall increase in EI scores, with a significant improvement in patient satisfaction. These findings suggest important potential benefits for both staff and their patients.